Evaluation of the cytotoxicity of cationic polymers on glioblastoma cancer stem cells - McCartin, Conor; Blumberger, Juliette; Dussouillez, Candice; Fernandez de Larrinoa, Patricia; Dontenwill, Monique; Herold-Mende, Christel; Lavalle, Philippe; Heurtault, Béatrice; Bellemin-Laponnaz, Stéphane; Fournel, Sylvie; Kichler, Antoine (Journal of Functional Biomaterials, 2023)
Cationic polymers such as polyethylenimine (PEI) have found a pervasive place in laboratories across the world as gene delivery agents. However, their applications are not limited to this role, having found a place as delivery agents for drugs, in complexes known as polymer-drug conjugates (PDCs). Yet a potentially underexplored domain of research is in their inherent potential as anti-cancer therapeutic agents, which has been indicated by several studies. Even more interesting is the recent observation that certain polycations may present a significantly greater toxicity towards the clinically important cancer stem cell (CSC) niche than towards more differentiated bulk tumour cells. These cells, which possess the stem-like characteristics of self-renewal and differentiation, are highly implicated in cancer drug resistance, tumour recurrence and poor clinical prognosis. The search for compounds which may target and eliminate these cells is thus of great research interest. As such, the observation in our previous study on a PEI-based PDC which showed a considerably higher toxicity of PEI towards glioblastoma CSCs (GSCs) than on more differentiated glioma (U87) cells led us to investigate other cationic polymers for a similar effect. The evaluation of the toxicity of a range of different types of polycations, and an investigation into the potential source of GSC’s sensitivity to such compounds is thus described.